1977
DOI: 10.1093/jaoac/60.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectral Confirmation of Aflatoxins

Abstract: Two methods for mass spectral (MS) confirmation of aflatoxins in agricultural products and in physiological fluids are described. In the first method, electron ionization (EI) mass spectra are obtained following isolation by thin layer chromatography (TLC) and compared with available reference mass spectra to provide structural confirmation. Extensive sample cleanup is required for confirmation at the 10—1000 ppb level and minimum sample size is 10—50 ng aflatoxin isolated by TLC. The second method restricts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Thus, substantially all of the analytic error is assigned to the use of the affinity column. In testing the HPLC column it was noted that aflatoxin would adsorb on newly purchased glassware (Haddon et al, 1977). This problem was solved by silination (surface deactivation) of the volumetric flasks using Sigmacote (Sigma Chemical Co., St. Louis, MO; instructions available from Sigma).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, substantially all of the analytic error is assigned to the use of the affinity column. In testing the HPLC column it was noted that aflatoxin would adsorb on newly purchased glassware (Haddon et al, 1977). This problem was solved by silination (surface deactivation) of the volumetric flasks using Sigmacote (Sigma Chemical Co., St. Louis, MO; instructions available from Sigma).…”
Section: Resultsmentioning
confidence: 99%
“…The procedure required a large on plate mass of aflatoxin B 1 , yet it did not work for other aflatoxins. Attempts to couple TLC with mass spectrometry for more specific identification were reported by Haddon et al [181,182], Brumley et al [183], Park et al [184] and Tripathi et al [185]. However, aflatoxins were unable to be directly analyzed by MS requiring extensive clean-up steps to remove aflatoxins from the plate and purified prior to MS analysis.…”
Section: Thin Layer Chromatographymentioning
confidence: 99%
“…Initially, aflatoxin confirmation was performed by bioassays [ 248 ], which was an indirect and time-consuming approach and soon replaced by techniques based on physicochemical properties of aflatoxins (e.g., 2D-TLC, chemical derivatization and FLD) [ 211 , 249 , 250 ]. When MS became available, negative chemical ionization MS- [ 182 ], gas chromatography (GC)–MS- [ 251 ] and eventually, LC-MS-based confirmation was adopted [ 136 , 252 ] by private and government laboratories.…”
Section: Chromatographymentioning
confidence: 99%
“…This method employs a two-dimensional TLC cleanup step. Previously, Haddon et al (1977) reported electron ionization analysis of aflatoxins Bx and Mx at resolution above 5000 in samples introduced through the direct insertion probe.…”
mentioning
confidence: 99%